PENGARUH PROFITABILITAS, LEVERAGE DAN MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Ana Mardiana; Jayanti Jayanti; Fransiskus Randa; Excel Limbunan (Tangible Journal, 2020)
This research aims to examine the influence of profitability, leverage, the composition of the independent board of commissioners and institutional ownership on the disclosure of corporate social responsibility to manufacturing companies listed on the Indonesia Stock Exchange. The population used in this research are all manufacturing companies listed on the Indonesia Stock Exchange with the research period 2015-2017. The method of determining the sample using purposive sampling with certain criteria and using secondary data in the form of company financial statements. This research use multiple linear analysis method. The results of this research indicate that profitability has a significant positive effect which means that the higher the level of profitability, the higher the disclosure of corporate social responsibility. Leverage has a negative effect but is not significant which means that the higher the leverage, the lower the disclosure of corporate social responsibility. The composition of the independent board of commissioners has a significant positive effect which means that the authority possessed by the board of commissioners can provide a strong enough influence to emphasize management to disclose corporate social responsibility. Institutional ownership has a positive but not significant influence which means that although it is considered very capable of overseeing and managing its investments, institutions as owners and one of the stakeholders have no influence on disclosure of corporate social responsibility.